Expression and purification of four truncated 56 kDa antigens from Orientia tsutsugamushi in Escherichia coli - Lan Anh, Le Thi; Toan, Trinh Van; Giang, Pham Thi Ha; Nga, Bui Thi Thanh; Cuong, Vo Viet; Nhung, Ho Thi Hong; Trang, Nguyen Le Huyen; Khang, Dinh Duy (Vietnam Journal of Biotechnology, 2018)
Scrub typhus is an acute febrile illness caused by Orientia tsutsugamushi, transmitted to humans by the bite of the larva of trombiculid mites. Diagnosis of scrub typhus is normally based on the clinical presentations. However, it is difficult to differentiate scrub typhus from other acute febrile illnesses, such as dengue fever, malaria and leptospirosis due to similar symptoms. For differential diagnosis of scrub typhus from other acute febrile diseases, a rapid and reliable serological diagnosis is important. In order to produce an ELISA kit for detection of antibodies against O. tsutsugamushi in Vietnam, four truncated 56 kDa antigenic genes of O. tsutsugamushi including Karp (HT-09), Gilliam (HT-11), TA763 (HT-49), and Kato (YB-50) íolated from the most prevalent cases in Vietnam were cloned and expressed in E. coli Rosetta 1 cells. The recombinant proteins formed inclusion bodies when expressed in E. coli. The recombinant 56 kDa proteins in insoluble form were solubilized in 6M urea and were successfully purified by Ni2+affinity column. The purity of four recombinant proteins,HT-09, HT-11, HT-49 and YB-50,reached more than 95% and their concentrations are 12,57 mg/ml; 11,6 mg/ml; 8,98 mg/ml và 8,02 mg/ml, respectively.